Bioassay of Glutathione S-transferase Antibody-Antigen Interactions Using Microcantilever Sensor - Xue, Changguo; Teng, Yanhua; Ye, Zhilin; Wang, Dongya; Wu, Xiuju; Wang, Rui; Lv, Zhili; Zhang, Mingxu (Asian Journal of Chemistry, 2013)
In this study, a real-time detection of glutathione S-transferase antigen and glutathione S-transferase antibody binding using a microcantilever sensor is reported. Glutathione S-transferase was immobilized onto microfabricated cantilever gold-coated surfaces by using thiol self-assembled monolayer. Consequently, the deflections of the microcantilever corresponding to the process of injecting anti-glutathione S-transferase antibody were generated, which was measured by using optical lever technique. An enzyme linked immunosorbent assay was used to determine the presence of an active antibody coating and to monitor the lifetime and stability of the immobilized antibody. This label-free method affords a new way to monitor various biomolecules interactions.